A Model of Unemployment Duration with Variable Search Intensity - Yoon, Bong Joon (The Review of Economics and Statistics, 1981)
A CCORDING to the standard job search model,I a job searcher knows the distribution function of wage offers available to him in the labor market and the fixed search cost of an offer per period. Given this knowledge, the searcher draws an offer and then weighs it against the possibility of better future offers. If the expected gain from searching for the next (future) offer exceeds the search cost, the current offer is rejected; and the individual remains unemployed. The entire search process, i.e., the duration of unemployment, ends when the searcher obtains an acceptable offer. Thus, the standard search model focuses on the unemployment duration as a result of the searcher's rejection of job offers. Consequently, lower search cost is regarded as a major deterrent to shortening unemployment duration since it encourages the searcher to reject offers. Another important factor affecting unemployment duration, which has not been given adequate attention in the standard model, is the time elapsed in searching (search time) for an offer. Most determinants of the search time for an offer, e.g., labor market conditions and socio-economic characteristics of the searcher, are beyond his control over the duration of unemployment. However, the search time for an offer is not entirely exogenous to the searcher. It can be shortened as he intensifies search effort. Raising search intensity, however, is costly; and it increases the search cost for an offer. This contrasts with the fixed search cost assumption built into the standard model. Thus, the searcher should choose an optimal level of search intensity to maximize the net return from job search. This paper extends the standard search model in order to investigate the role of search time for an offer in the determination of unemployment duration. An econometric model of unemployment duration with variable search intensity is formulated in section II. The model distinguishes between two components of unemployment duration which are related to each other: (i) the search time for an offer and (ii) the unemployment duration due to rejection of offers. It also decomposes the search cost of an offer into a fixed cost and a variable cost, which depends on the level of search intensity. Under the assumption that the elasticity of the mean search time for an offer with respect to search intensity is greater than 1 but less than 0, several results are shown: First, higher fixed search cost per unit time lowers the mean duration of unemployment as usual. Second, the unit cost of search intensity is positively related to unemployment duration, contrary to the implication of the standard model. That is, as the unit cost of search intensity rises, the search cost of an offer increases; but the duration of unemployment does not decrease. This is because the resulting decrease in search intensity increases the first component of unemployment duration (search time for an offer), which more than compensates for the decrease in the second component due to the higher search cost of an offer. Section III presents empirical investigations on the duration of unemployment, which are shown to be consistent with the theoretical contentions of section II. Finally, conclusions are summarized in section IV.